PERSEPSI PESERTA DIDIK TERHADAP PELAKSANAAN KONSELING INDIVIDUAL DI SEKOLAH - Syifa Syifa; Nadia Aulia Nadhiroh; Nandang Budiman (AL - IBRAH, 2023)
Abstract : The scope of discussion in this paper concerns the implementation of individual counseling services in schools and students' perceptions of the implementation of individual counseling services. This study aims to describe and find out how students perceive individual counseling at school. The systematic literature review (SLR) method was chosen in the preparation of this article. Individual counseling is carried out to help students who have problems. The steps in carrying out the SLR method are compiling statements related to the mini research being carried out, conducting searches with systematic literature reviews, identifying, assessing, analyzing, and compiling reports. There are results from non-research that have been carried out from several previous studies in various schools in Indonesia, namely that there are various perceptions such as: 1) students feel happy following the implementation of individual counseling because it can help solve problems, 2) students feel afraid to answer and asked questions when carrying out counseling because of tension, 3) has a negative perception of the counseling teacher which makes him reluctant to do counseling 4) is more comfortable telling about his problems to friends. Keywords: Learners, Perceptions, Guidance and Counseling